2015
DOI: 10.1128/jvi.00232-15
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A Virus Panhandle Structure Is Directly Involved in RIG-I Activation and Interferon Induction

Abstract: Retinoic acid-inducible gene I (RIG-I) is an important innate immune sensor that recognizes viral RNA in the cytoplasm. Its nonself recognition largely depends on the unique RNA structures imposed by viral RNA. The panhandle structure residing in the influenza A virus (IAV) genome, whose primary function is to serve as the viral promoter for transcription and replication, has been proposed to be a RIG-I agonist. However, this has never been proved experimentally. Here, we employed multiple approaches to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
110
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(114 citation statements)
references
References 65 publications
(89 reference statements)
2
110
0
Order By: Relevance
“…RIG-I and MDA5 can bind mitochondrial Cardif (also known as MAVS, IPS-1, and VISA) through caspase recruitment domains, initiating downstream signaling that leads to IFN induction [20]. In the case of IAV infections, RIG-I and TLR3 are identified as two major PRRs induced by IAV infection [21,22]. RIG-I senses the accumulation of IAV 5 0 -triphosphate RNA, which leads to the activation of type-I IFN [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RIG-I and MDA5 can bind mitochondrial Cardif (also known as MAVS, IPS-1, and VISA) through caspase recruitment domains, initiating downstream signaling that leads to IFN induction [20]. In the case of IAV infections, RIG-I and TLR3 are identified as two major PRRs induced by IAV infection [21,22]. RIG-I senses the accumulation of IAV 5 0 -triphosphate RNA, which leads to the activation of type-I IFN [21].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of IAV infections, RIG-I and TLR3 are identified as two major PRRs induced by IAV infection [21,22]. RIG-I senses the accumulation of IAV 5 0 -triphosphate RNA, which leads to the activation of type-I IFN [21]. In contrast, TLR3 activates proinflammatory cytokines in response to IAV infection [22].…”
Section: Discussionmentioning
confidence: 99%
“…RIG-I possesses two N-terminal caspase recruitment domains (CARDs), a central RNA helicase domain of the DExD/H box type, and a C-terminal domain (CTD) that is important for RNA ligand binding (9). RIG-I responds strongly to 5=-end-triphosphorylated dsRNA structures (5=-ppp-dsRNA), like the "panhandle," which can be formed by complementary sequences of the 5= and 3= termini of the FLUAV genome (10)(11)(12). The binding of RIG-I to the FLUAV panhandle occurs immediately after the RNPs enter the host cell and can impose a direct antiviral effect via the disassembling of the RdRP complex (13).…”
Section: Influenza a Virus And Rig-imentioning
confidence: 99%
“…One study suggested that influenza A virus (IAV) RNA synthesis and nuclear export but not viral replication trigger IFN gene expression (12). Other studies have proposed that RIG-I can recognize the incoming negativesense RNA virus via its 5=-triphosphorylated genomic RNA, even though it is bound by NP proteins and the viral RNA polymerase complex (13)(14)(15). It has also been suggested that the incoming influenza A virus carries certain viral structures that inhibit RIG-I activation and IFN induction, even though the viral RNA is recognized by RIG-I at the time of entry into the cytosol (16).…”
mentioning
confidence: 99%